(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article provides a scientific analysis of theoretical and practical aspects of the tactics of detention of wanted terrorists and extremists, as one of the necessary means of counteracting terrorism and extremism of international, transnational nature. Based on the norms of criminal procedure, operational-search legislation, taking into account the features of forensic and operational-search tactics of detention of wanted terrorists and extremists, the opinions of scientists, proceduralists and criminologists who conducted research in the area under consideration are given. The conducted analysis of the algorithm of actions of employees carrying out direct detention of wanted terrorists and extremists showed the main directions of detention of wanted defendants of this category, indicating the optimal mechanism for implementing the function of detention of wanted defendants.